FKKT Navdih Znanosti (University of Maribor Press, 2019)
FCCE Inspired by Science. The brochure contains all of the FCCC’s essential information, faculty vision, study programs, access requirements, student activities, course syllabuses and labs presentations: employees, research areas, the most important achievements, updated the most important publications, cooperation with institutions and companies, ongoing projects and research equipment.